Risk factors for the leakage of chemotherapeutic agents into systemic circulation after transcatheter arterial chemoembolization of hepatocellular carcinoma - Ming-Yen Hsieh; Zu-Yau Lin; Su-Hwei Chen; Wan-Long Chuang (Kaohsiung Journal of Medical Sciences, 2011)
This prospective study was to investigate the possible risk factors for the leakage of chemotherapeutic agent into the systemic circulation after transcatheter arterial chemoembolization (TACE) of hepatocellular carcinoma (HCC). Peripheral plasma concentrations of chemotherapeutic agents were determined at 1 hour and 72 hours after TACE by high-performance liquid chromatography in 53 patients. HCC were divided into three types namely single nodule (<5 cm), multiple nodules (all <5 cm), and main nodule measuring 5 cm or more. Forty-four patients (83%) showed detectable chemotherapeutic concentrations within 72 hours after TACE. Patients with single nodular-type HCC had lower incidence of detectable plasma chemotherapeutic agents after TACE than the other two groups (all p<0.05). The injected doses of lipiodol, epirubicin, and mitomycin C were lower in patients without detection than in patients with detectable chemotherapeutic agents (all p<0.05). Multivariate logistic regression showed that tumor type and injected dose of lipiodol were two independent risk factors for the leakage of mitomycin C at 1 hour after TACE (all p<0.05), and the injected dose of mitomycin C was the risk factor for the leakage of epirubicin at 1 hour after TACE (p<0.05). In conclusion, multiple nodular type and large nodule measuring 5 cm or more have a risk of leakage of mitomycin C after TACE. Injected dose of lipiodol and mitomycin C as risk factor for the leakage of mitomycin C and epirubicin respectively may be because of competition of their injected volume within the limited space of target.